Effect of heat treatment on corrosion resistance of Al2O3-TiO2 ceramic coating impregnated with aluminum phosphate - Nguyen Van, Tuan; Nguyen, Tuan Anh; Pham Thi, Ha; Pham Thi, Ly; Nguyen Thi, Phuong; Le Thu, Quy (Vietnam Journal of Science and Technology, 2024)
The atmospheric plasma spray process (APS) is a well-established and widely employed technology used to create various types of coating for the fabrication of numerous industrial applications. Speciallity, this process is considered as a suitable technique for fabricating ceramic coatings. However, the structure of thermal spray coatings consists of particles, semi-molten particles, oxides, pores, and cracks that signiﬁcantly inﬂuence the coating properties, especially their erosion-corrosion resistance. In this study, the Al2O3-40TiO2 coating applied by APS was penetrated with aluminum phosphate (APP) by ultrasonic excitation method, and then, the effect of heat treatment after the sealing on corrosion protection of Al2O3-40TiO2 ceramic coating was investigated. The results show that, after being impregnated with APP, the heat treatment at 800 oC assures the coating a lower porosity and better corrosion resistance than heat treatments at 400 and 600 oC. The existence of the durable crystalline phases Al(PO3)3 (Cubic), Al2P6O18 (Monoclinic), and AlPO4 (Orthorhombic) on the surface of the sample heat-treated at 800 oC has contributed to enhancing the corrosion resistance of the Al2O3-40TiO2 coating.